The Implementation of Learning Activities in the Block Center at the Integrated Islamic Kindergarten – Nur Hikmah - Firdaus, Fattah; Utomo, Haryadi; Unsah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The block center is an essential component of kindergarten learning activities, functioning to develop children’s motor, cognitive, social, emotional, and spiritual abilities in an integrated manner. In the context of integrated Islamic education, the block center serves not only as a medium for constructive play but also as an effective tool for instilling Islamic values such as cooperation, honesty, discipline, and responsibility. This study aims to describe the implementation of learning activities in the Block Center of the Integrated Islamic Kindergarten – Nur Hikmah, emphasizing the integration between children’s developmental aspects and Islamic values. This research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The data were analyzed interactively through the stages of reduction, presentation, and conclusion drawing. The findings reveal that learning in the Block Center is conducted through the learning by playing approach and the Beyond Centers and Circle Time (BCCT) model, positioning children as active subjects. Teachers act as facilitators and motivators through scaffolding stages before, during, and after play, integrating Islamic values such as prayer, mutual respect, and gratitude. Activities involving building and designing structures with blocks enhance children’s motor coordination, logical thinking, creativity, and social skills. The internalization of Islamic values nurtures spirituality, empathy, and discipline. In conclusion, learning in the Block Center plays a vital role in shaping intelligent, virtuous, and 21st-century-skilled children while reinforcing the core objective of Islamic education—to cultivate insan kamil (a well-rounded human being) from early childhood.